MICROCEFALIA EM RECÉM-NASCIDOS: ANTES E APÓS EPIDEMIA PELO VÍRUS ZIKA. - CÂMARA, Ana Patricia Barros (2018)
Microcephaly is a clinical finding characterized by a cephalic perimeter (PC) lower than that expected for age and gender (PC less than -2 standard deviation below the mean). They can be identified at birth (congenital microcephaly) or after delivery (secondary microcephaly). When in microcephaly the growth of the brain does not follow the growth of the rest of the body of the newborn (somatic growth) is then denominated disproportional microcephaly and when the PC is less than -3 standard deviation for the gestational age and the sex is characterized like severe microcephaly. The causes of microcephaly are multiple, but intrauterine infections are more frequent, for example: syphilis, rubella, cytomegalovirus, herpes simplex virus and more recently Zika virus (ZIKV). At the end of 2015 there was an unexpected increase in the number of microcephaly in newborns in Brazil, and as the main suspect the vertical transmission of ZIKV. The objective of this study was to analyze the prevalence of microcephaly, severe microcephaly and disproportionate microcephaly in relation to weight and length in newborns in Ribeirão Preto / SP and in São Luís / MA, before (2010) and after (2016) a epidemic by the Zika virus. And as specific objectives: to estimate the prevalence of microcephaly and severe microcephaly at birth in Ribeirão Preto and São Luís; to compare the prevalence of microcephaly and severe microcephaly according to proportionality in relation to the length and weight of the newborn in Ribeirão Preto and São Luís; and to compare the number of cases of microcephaly and severe microcephaly expected with those occurring in Ribeirão Preto and São Luís. A cross-sectional study was conducted with data collected in maternity hospitals in 2010 (Study of Brazilian Cohorts in Ribeirão Preto and São Luís) and in 2016. For the sample of the study in 2010, the newborns of hospital delivery from five maternity hospitals in Ribeirão Preto and four in São Luís, from mothers residing in the municipalities under study, from January to December were included. In 2016, the data were collected in the same maternities used in the first year of the study. All live births over 500 g or 20 weeks of gestational age were included. The variables used were sex, cephalic perimeter, weight, length of newborns and gestational age at birth. The categorical quantitative variables were presented by frequencies and percentages and the normality of the numerical variables was verified by the Shapiro Wilk test, Boxplot analysis and histogram; as all presented normal distribution were presented in mean and standard deviation. The measure of proportionality between head circumference and z-score of length or weight was calculated to find out if head growth did not follow somatic growth. In order to calculate the estimated number of expected cases of microcephaly and severe microcephaly, the following formula was used: prevalence of number of cases times the number of live births in the respective years (reported by SINASC) divided by 100. In the statistical analyzes, the prevalences with the Chi-square test for independent samples; for all analyzes a significance level of 5% was considered. The data were analyzed in the program STATA®14. Using the criteria of the Ministry of Health, in Ribeirão Preto the prevalence of newborns with microcephaly at birth was 3.15% in 2010 and 1.67% in 2016; the prevalence of severe microcephaly was 0.75% in 2010 and 0.43% in 2016. In the city of São Luís, in 2010, 4.12% were born with microcephaly and 0.78% with severe microcephaly; in 2016 the prevalence of microcephaly decreased to 1.65% and that of severe microcephaly to 0.32%. According to INTERGROWTH 21th, the prevalence of severe microcephaly was higher in 2010 than in 2016 in the two cities under study and the drop in microcephaly prevalence was more significant in São Luís. As for newborns with microcephaly in 2010, 1, 57% presented disproportionate microcephaly in relation to the length and 1.80% in relation to the weight in the city of Ribeirão Preto; in São Luís the values were higher, 2.73% in relation to the length and 2.94% in relation to the weight. We observed that in the two cities under study the expected number of cases of microcephaly at birth was greater than the total number of cases occurred. We concluded that the prevalence of microcephaly and severe microcephaly was higher before the epidemic by the Zika virus (2010) compared to 2016; among these newborns the highest prevalence was of disproportionate microcephaly in relation to somatic growth in the two cities in the periods studied and the number of cases that occurred in both cities was smaller than the number of expected cases.